Hacia la investigación en docencia: orientaciones básicas - Mora Vargas, Ana Isabel (2012)
This article offers guidelines so that education students can incorporate a positive attitude towards research in their academic experience. In this way, they would be able to later transfer such attitude to their professional performance. Four topics are proposed in this article: the teachingresearch relationship, the educational diagnosis, the structure of a research report, and a guide for citing bibliographical references. Each of the topics summarizes the author’s experience both as a teacher and researcher at the higher education level. Some basic theoretical foundations and suggested activities for practical application are also offered.